Architecture of the intestinal crypts of the payers’ patches of the albino rats’ small intestine. - V. H. Hryn; Y. P. Kostylenko (Морфологія, 2019)
Background. In the Peyer’s patches, intestinal crypts are topographically differentiated with respect to their lymphoid nodules. Consequently, two types are distinguished. The first type is associated with the lymphoid tissue of the corresponding nodules, and the second one is located outside of them. Objective. To study the features of architecture of the intestinal crypts of the Payer’s patches of albino rats’ small intestine. Methods. 30 mature albino male rats weighted 200,0±20,0 g were involved into the study. Sections of the small intestine with Peyer's patches were fixed in 10% neutral buffered formalin solution. Subsequently, serial paraffin sections of 4 μm thick (Microm HM 325), stained with hematoxylin-eosin, were obtained using the conventional histological methods. Another part of the preparations was plasticized in the epoxy. The analysis of the obtained preparations was carried out using the MBS-9 binocular magnifier and “Konus” light microscope equipped with Sigeta DCM-900 9.0MP digital microphotographic attachment, object-micrometer Sigeta X 1 mm/100 Div.x0.01mm. Results. Payer’s patches contain two types of the intestinal crypts, discrete by the bundles of smooth muscle fibers. Lymphoid-associated crypts (i.e., intranodular) are actually offshoots of the extranodular crypt network laid at the base of the intestinal villi of the Peyer’s patches. Their penetration into the thickness of the lymphoid nodules occurs around their circumference through local splitting of the bundles of smooth muscle fibers, as a result of which they appear in the thickness of their peripheral regions, corresponding to T-dependent zones. Conclusions. Despite the common origin, these crypts, differing in localization, differ in thickness (the diameter of lymphoid-associated crypts is on the average of 70 μm, while extranodular crypts are 10 μm narrower in the diameter), as well as in the cytological composition and contents of the internal lumen.